2012
DOI: 10.1007/s10637-012-9867-x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic modeling of Sepantronium bromide (YM155), a small molecule survivin suppressant, in patients with non-small cell lung cancer, hormone refractory prostate cancer, or unresectable stage III or IV melanoma

Abstract: SummaryPurpose Population pharmacokinetics (PK) of sepantronium bromide (YM155) was characterized in patients with non-small cell lung cancer, hormone refractory prostate cancer, or unresectable stage III or IV melanoma and enrolled in one of three phase 2 studies conducted in Europe or the U.S. Method Sepantronium was administered as a continuous intravenous infusion (CIVI) at 4.8 mg/m2/day over 7 days every 21 days. Population PK analysis was performed using a linear one-compartment model involving total bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…This is in the range of therapeutically achievable plasma levels that were documented to reach about 50 nM. 20, 21, 22 Notably, animal models indicated that the YM155 concentrations in tumor tissues are likely to be higher than those found in the plasma. 3, 23 Previously, YM155 IC50 values were reported to range from 3.2 to 11 nM in melanoma cells 24 and from 2 to 50 nM in multiple myeloma cells.…”
Section: Discussionmentioning
confidence: 88%
“…This is in the range of therapeutically achievable plasma levels that were documented to reach about 50 nM. 20, 21, 22 Notably, animal models indicated that the YM155 concentrations in tumor tissues are likely to be higher than those found in the plasma. 3, 23 Previously, YM155 IC50 values were reported to range from 3.2 to 11 nM in melanoma cells 24 and from 2 to 50 nM in multiple myeloma cells.…”
Section: Discussionmentioning
confidence: 88%
“…Several phase I and II clinical trials ofYM155 combined with chemotherapeutic agents have been conducted in patients with breast, prostate, non-small-cell lung cancer, non–Hodgkin lymphoma, and colorectal cancer(46,47). Nonetheless, the portfolio of survivin antagonists or suppressors available for clinical testing, particularly in SCCHN, is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…YM155 has entered a few early stage clinical trials for the treatment of advanced cancers. The preliminary results have shown a potent anti-tumor growth activity (11, 12, 32, 33). However, YM155 has yet to be fully tested in human pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%